PENERAPAN COACHING DALAM SUPERVISI AKADEMIK - Mabruroh; Atikah, Cucu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to find out about the implementation of academic supervision in schools, related to supervision principles, approaches, techniques, supervision models, instruments, stages of supervision and TIRTA model coaching techniques in academic supervision carried out by school principals for teachers. The method used is a literature review. sourced from books and journals as well as modules relevant to this research. This research provides a good contribution to the development of coaching model supervision that focuses on the context of academic supervision in schools. These findings can provide practical guidance for education practitioners, school principals, teachers and policy developers in improving the quality of learning in schools through innovative approaches, models and supervision techniques.